Studies on synthesis of quinonylidene Hoveyda‐type complexes. (20th March 2015) - Grudzień, Krzysztof; Barbasiewicz, Michał
<x xml:space="preserve">Abstract</x> In a quest of redox‐switchable metathesis catalysts we attempted synthesis of ruthenium quinonylidene complexes using two synthetic pathways. First, Hoveyda‐type complexes bearing chelating benzylidene and naphthylidene ligands substituted with two alkoxy/hydroxy groups were synthesized and characterized. The catalysts were tested in model ring‐closing metathesis reactions, and displayed interesting correlations between structure and catalytic activity. Unfortunately, numerous attempts at oxidation of the complexes to derivatives of benzo‐ and naphthoquinone were unsuccessful. However, the second approach, using exchange reaction of ruthenium precursor with vinylquinone ligand, gave a transient unstable product observed with 1H NMR. The experimental data suggest that conjugation of electron‐deficient quinones to the ruthenium centre results in intrinsically unstable species, which undergo secondary reactions under ambient conditions. Copyright © 2015 John Wiley & Sons, Ltd.